Near‐Bed Flow Turbulence Beneath Ice Cover Under Varying Hydrological Conditions: A 9‐Year Field Measurement‐Based Analysis From a Meander Bend - Lintunen, Karoliina; Vilhonen, Essi; Takala, Tuure; Blåfield, Linnea; Kasvi, Elina; Lotsari, Eliisa; Alho, Petteri (American Geophysical Union (AGU), 2026)
Climate change alters hydrological and ice conditions, but how these changes affect turbulence beneath ice cover has been poorly studied. This study presents a multi-year observational analysis of near-bed turbulence under ice cover in a subarctic meandering river reach. Measurements were obtained using an Acoustic Doppler Current Profiler (ADCP) and an Acoustic Doppler Velocimeter (ADV), which provided flow parameters and enabled the calculation of turbulence variables, together with a camera to capture visual information on bedforms. In the analyses, we considered the effects of water column height, ice thickness, discharge, and riverbed forms on near-bed turbulence. The results show that water column height beneath ice cover is the most consistent factor controlling turbulence because near-bed turbulence generally decreases as the water column height increases. Conditions during ice formation affected the resulting water column height and thus indirectly influenced near-bed turbulence. Turbulence was most pronounced in shallow upstream and inner-bend sections of the meander whereas deeper areas exhibited reduced turbulence. Discharge modulated the ice effect, with low to moderate winter flows amplifying ice's influence on near-bed turbulence whereas higher flows tended to override it. Thicker ice cover was associated with reduced turbulent kinetic energy (TKE) but with increased streamwise and vertical turbulence intensities during low-flow years. These results suggest that ongoing shifts in winter ice regimes and flow seasonality may alter under-ice turbulence, with consequent effects on sediment transport and channel morphodynamics. Uncertainty in comparisons arises from instrument limitations, field conditions, and interannual variability in hydrological regimes.